2020
DOI: 10.1080/20013078.2019.1710899
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the evolution of circulating exosomal‐PD‐L1 to monitor melanoma patients

Abstract: In the era of immunotherapies there is an urgent need to implement the use of circulating biomarkers in clinical practice to facilitate personalized therapy and to predict treatment response. We conducted a prospective study to evaluate the usefulness of circulating exosomal-PD-L1 in melanoma patients' follow-up. We studied the dynamics of exosomal-PD-L1 from 100 melanoma patients by using an enzyme-linked immunosorbent assay. We found that PD-L1 was secreted through exosomes by melanoma cells. Exosomes carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(214 citation statements)
references
References 29 publications
9
190
1
3
Order By: Relevance
“…Soluble PD-L1 (sPD-L1) is frequently detected in the blood of cancer patients. Three mechanisms can contribute to the release of PD-L1 into circulation: alternatively spliced transcripts [ 153 , 154 ], release of PD-L1 associated with extracellular vesicles such as exosomes [ 155 , 156 ] and proteolytical cleavage from the surface of PD-L1-expressing cancer- and non-cancer cells [ 157 ].…”
Section: Regulation Pd-l1 Protein Expressionmentioning
confidence: 99%
“…Soluble PD-L1 (sPD-L1) is frequently detected in the blood of cancer patients. Three mechanisms can contribute to the release of PD-L1 into circulation: alternatively spliced transcripts [ 153 , 154 ], release of PD-L1 associated with extracellular vesicles such as exosomes [ 155 , 156 ] and proteolytical cleavage from the surface of PD-L1-expressing cancer- and non-cancer cells [ 157 ].…”
Section: Regulation Pd-l1 Protein Expressionmentioning
confidence: 99%
“…Several studies revealed the presence of PD-L1 in exosomes isolated from blood samples of patients with cancer, and the level of PD-L1 correlates with pathological features of these patients [23,24,39,40]. Chen et al reported metastatic melanomas released exosomes, delivering PD-L1 on their surface.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated basal levels of soluble PD-L1 in the plasma of melanoma patients was associated with progressive disease [95]. Furthermore, the measurement of PD-L1 in EV could help to predict the response to ICI, demonstrating an advantage of the detection in EV over tumor biopsies [96]. Melanoma patients responding to pembrolizumab could be distinguished from non-responders by increased levels of EV PD-L1 at 3 to 6 weeks after the start of therapy [97].…”
Section: Predicting the Response To The Ici Therapymentioning
confidence: 99%